Recommendations for the wise use of urban and peri-urban wetlands in Kolkata, India - Amerasinghe, Priyanie H.; Dey, Dipayan (CGIAR Research Program on Water, Land and Ecosystems, 2018)
Urban and peri-urban wetlands provide services seen and unseen to millions of people and to the environment on which we rely. Wetlands support people’s needs for food, water, fiber, fuel, medicine and livelihoods. Also, they provide vital “ecosystem services” such as purifying water, mitigating floods, absorbing carbon, providing cultural and recreational spaces, and ensuring there are nutrients for farming. However, wetlands face serious risks. They are confronted by a range of threats flowing from modern life, such as urban development, pollution and agricultural use. To protect these crucial areas, this brief offers recommendations on the wise use of urban and peri-urban wetlands in Kolkata, India, as guidance to the Department of Environment in West Bengal and other decision makers. The recommendations are based on two sources. First, a research project carried out in Kolkata from 2012 to 2016 assessed the current status and use of wetlands in peri-urban areas (Figure 1). In this study, we reviewed how communities depend on wetlands for their livelihoods as well as how this dependency is affected by urbanization and the sustainable intensification of agriculture. Second, representatives from more than 10 government and nongovernmental institutions in Kolkata reviewed the results of this study and provided feedback. The final conclusions provide guidance for future policy change for the wise use of wetlands in Kolkata as well as in urban and peri-urban areas elsewhere in India.